Shielding of Lipid Nanoparticles for siRNA Delivery: Impact on Physicochemical Properties, Cytokine Induction, and Efficacy - Varun Kumar; June Qin; Yongfeng Jiang; Richard G Duncan; Benjamin Brigham; Shannon Fishman; Jayaprakash K Nair; Akin Akinc; Scott A Barros; Pia V Kasperkovitz (Elsevier, 2014)
Formulation of short interfering RNA (siRNA) into multicomponent lipid nanoparticles (LNP) is an effective strategy for hepatic delivery and therapeutic gene silencing. This study systematically evaluated the effect of polyethylene glycol (PEG) density on LNP physicochemical properties, innate immune response stimulation, and in vivo efficacy. Increased PEG density not only shielded LNP surface charge but also reduced hemolytic activity, suggesting the formation of a steric barrier. In addition, increasing the PEG density reduced LNP immunostimulatory potential as reflected in cytokine induction both in vivo and in vitro. Higher PEG density also hindered in vivo efficacy, presumably due to reduced association with apolipoprotein E (ApoE), a protein which serves as an endogenous targeting ligand to hepatocytes. This effect could be overcome by incorporating an exogenous targeting ligand into the highly shielded LNPs, thereby circumventing the requirement for ApoE association. Therefore, these studies provide useful information for the rational design of LNP-based siRNA delivery systems with an optimal safety and efficacy profile.